Family-centered care from the perspective of nurses in the Neonatal Intensive Care Unit - Thaís Regina Gomes da Silva; Bruna Figueiredo Manzo; Fernanda Cristina Custodia de Faria Fiorete; Paloma Morais Silva (Rev Rene)
Objective: to describe the challenges and strategies for implementation of Family-centered  Care in the in the care of newborns hospitalized in the Intensive Care Unit from the perspective of nurses. Methods: qualitative study conducted in the Neonatal Intensive Care Unit of a public hospital. Fourteen nurses were interviewed. We used the technique of thematic content analysis. Results: the main aspects hindering the implementation of Family-centered Care were: lack of material resources, absence of parents in the unit and shortage of staff, which influenced directly in the assistance provided to the newborn and the family. To minimize the challenges, nurses mentioned strategies such as creating and updating protocols, training, continuing education programs, optimizing communication and meetings with families. Conclusion: the main challenges are related to human and material resources and infrastructure. Strategies mentioned were teamwork and continuous improvement.